2019
DOI: 10.3390/cells8121490
|View full text |Cite
|
Sign up to set email alerts
|

PC1/3 KD Macrophages Exhibit Resistance to the Inhibitory Effect of IL-10 and a Higher TLR4 Activation Rate, Leading to an Anti-Tumoral Phenotype

Abstract: During tumorigenesis, macrophages are recruited by tumors and orientated towards a pro-tumoral phenotype. One of the main anti-tumoral immunotherapy consists of their re-polarization in an anti-tumoral phenotype. We have demonstrated that the inhibition of proprotein convertase 1/3 combined with TLR4 activation in macrophages is a promising strategy. These macrophages display pro-inflammatory and anti-tumoral phenotypes. A hallmark is a stronger activation of the pro-inflammatory NFKB pathway. We believe that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…28 TLR4 was pivotal promoter of inflammation which related NF-kB and C3 signaling, and then released TNF-α and ILs, which can induce apoptosis of osteosarcoma cells. 10,11,31,32 However, whether the role of COLEC12 for inflammation in osteosarcoma is regulated by TLR4…”
Section: F I G U R Ementioning
confidence: 99%
“…28 TLR4 was pivotal promoter of inflammation which related NF-kB and C3 signaling, and then released TNF-α and ILs, which can induce apoptosis of osteosarcoma cells. 10,11,31,32 However, whether the role of COLEC12 for inflammation in osteosarcoma is regulated by TLR4…”
Section: F I G U R Ementioning
confidence: 99%
“…This revealed an essential role of PC1/3 in TLR4 trafficking. An over-expression of MYD88 was also observed in PC1/3 KD macrophages treated with LPS ( 36 ) ( Figure 3 ). As a consequence, a longer activation of the NF-κB signaling pathway was observed ( 28 ).…”
Section: Tlrs Signaling and Pcsmentioning
confidence: 80%
“…Following LPS stimulation, PC1/3 trafficked with TLR4 ( 27 ). Of note, PC1/3 knock down led to a quicker recycling of TLR4 at the cell surface ( 36 ) ( Figure 3 ). This revealed an essential role of PC1/3 in TLR4 trafficking.…”
Section: Tlrs Signaling and Pcsmentioning
confidence: 99%
“…In this context, it has been demonstrated that Furin and the proprotein convertase 1/3 (PC1/3) are two complementary targets for reinforcing the immune response [23][24][25][26][27][28][29][30]. Furin is critical for the maintenance of peripheral CD4 + Foxp3 + T regulatory cell-dependent immune tolerance and normal CD4 + T helper (Th) cell polarization in vivo [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…We established that PC1/ 3 KD macrophages secrete high quantities of extracellular vesicles (EVs) [25,27,29] which is even more important when TLR4 or TLR9 pathways are triggered in PC1/3 KD macrophages [27,28]. PC1/3 modulates GRAMD4 levels and thus regulate TLR9 trafficking, to modulate the inflammatory response [29]. Its inhibition reactivates the pro-inflammatory TLR MYD88 NFKB dependent pathway while the anti-inflammatory STAT3 pathway is downregulated [29].…”
Section: Introductionmentioning
confidence: 99%